Attenuating depression behavior by Centella asiatica extract & venlafaxine in mice induced through Forced swim and Tail suspension test - Kumar, Vinay; Tomar, Aakanksha; Singh, Bhulan Kumar; Nagarajan, Kandasamy; Machawal, Lalit; Bajaj, Umakant (International Journal of Pharmacology and Toxicology, 2013)
The present research work was planned to study the combination therapy of Centella asiatica and venlafaxine for antidepressant activity. Wistar albino mice of body weight 25-35g were used in the experiment. Depression was induced by Forced swim test (FST) and Tail suspension test (TST). Immobility, swimming and climbing time and locomotor activity were measured in FST and immobility time was measured in TST. Animals treated with venlafaxine (10 mg/kg) & Centella asiatica (100 mg/kg, 200mg/kg) & combination therapy venlafaxine (10 mg/kg) + Centella asiatica (200mg/kg) showed amelioration in swimming time and climbing time while immobility time was attenuated as compared to depression control group. Centella asiatica showed attenuation in immobility time in FST and TST. The finding of the present investigation reveals that combination of venlafaxine and had significant antidepressant effect then alone. In conclusion, Centella asiatica could be used along with venlafaxine because of their neuroprotective effect in depression.